Does work socialisation matter? Worker engagement in political activities, attachment to democracy and openness to immigration. Issue 2 (28th February 2021) - Ryan, Lorraine; Turner, Thomas
Abstract: The effects of work socialisation on worker engagement in political activities, attachment to democracy and openness to outsiders are explored in this article. Work environments are measured using firm size, unionisation and employee participation as significant factors that contribute to the development of democratic or authoritarian sentiment at work. Using data from the European Social Survey across 11 countries, we test whether work socialisation influences individuals' attitudes such as trust in the societal institutions of democracy, active involvement in political activities and openness to outsiders, particularly immigrants. Results indicate that individuals working in large organisations accompanied by higher levels of voice and participation at work are more likely to report greater political engagement, trust in politics, trust in people and openness to outsiders compared to workers in small organisations with low levels of voice and participation.